Islamic Law in Malaysia: how far does it extend? / Sheikh Mohd Tawfeek Badjenid Sheikh Hassan - Sheikh Hassan, Sheikh Mohd Tawfeek Badjenid (Faculty of Law, 1986)
Islamic Law should not and should never be made a 'sacred subject in silken covers' where only certain group of people are entitle to touch upon it or to discuss over it. Nor should Islamic Law regarded as an “ancient system” where its applicability is only relevant in ancient times with different situations and circumstances. Islamic Law should not be taken “lightly" and should never be practiced or enforced "partly" (for example only Islamic Family Law is Applied in Malaysia). Instead in upholding, applying and following the Islamic Law, it should be in the light of the true Islamic principles. The Quran provides; “If any do fail to judge by what Allah has revealed, they are unbelievers". "If any fail to judge by what Allah has revealed, they are wrongdoers”. "If any fail to judge by what Allah revealed, they are those who rebel". "It is not befitting for a believer, man or woman, when a matter has been decided by Allah and His messenger to have any option about their decision. If anymore disobeys Allah and His Messenger, he is indeed clearly on a wrong path". Then is it only a part of the Book that you believe in and do you reject the rest? But what is the reward for those among you who behave like this but disgrace in this life? And on the day of judgement they shall be consigned to the most grievous penalty. For God is not unmindful of what you do".